2005
DOI: 10.1111/j.1439-037x.2004.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Row Spacing and Plant Density Effects on Forage and Dry Matter Yield of Corn Hybrids (Zea mays L.)

Abstract: Irrigated field experiments were conducted in the Marmara region of Turkey in 2002 and 2003 to compare alternate 40 : 25 cm row spacings and conventional 65 cm with four different plant densities (65 000, 85 000, 105 000 and 125 000 plants ha−1) of three corn hybrids (DK‐585, ADA 95–10 and C‐955) in some morphological traits and forage and dry matter yield. Morphological traits such as plant height, leaf per plant, stem diameter, ear per plant and ear percentage were measured, forage and dry matter yield was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
20
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 14 publications
(24 reference statements)
14
20
2
Order By: Relevance
“…However, yield components were not significantly influenced by row spacing or plant density ( Table 1). It is similar to the results obtained by Turgut et al [2] as reported that row spacings and plant densities did not significantly affect corn yield components such as the number of ear per plant. It can be concluded that improved corn yield at the narrower rows or the higher plant densities was mainly du o increasing the number e t Phosphate biofertilizer did not significantly affect corn yield and yield components ( Table 1).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…However, yield components were not significantly influenced by row spacing or plant density ( Table 1). It is similar to the results obtained by Turgut et al [2] as reported that row spacings and plant densities did not significantly affect corn yield components such as the number of ear per plant. It can be concluded that improved corn yield at the narrower rows or the higher plant densities was mainly du o increasing the number e t Phosphate biofertilizer did not significantly affect corn yield and yield components ( Table 1).…”
Section: Resultssupporting
confidence: 82%
“…In this study, the highest corn yield was obtained at the highest plant density (90,000 plants·ha -1 ) as compared with lower plant densities. Generally, increasing plant density usually increases corn grain yield until an optimum number of plants per unit area is reached [2]. However, the optimal plant density level and row width for corn may vary with location [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation of the relationships under mild water stress is consistent with proportionate reductions in cell length and width reported in Tardieu et al (2000). By contrast, the differences in coefficients of equations where interplant competition occurred, are consistent with changes of carbohydrate storage pattern (Turgut et al, 2005;Pagano et al, 2007) and competitive effects causing etiolation (lengthening) of cells and organs at the expense of width (Bos et al, 2000;Andrieu et al, 2006).…”
Section: Allometric Relationships Between Organ Morphology and Its Bisupporting
confidence: 54%
“…According to the evaluations made about plant height, the effect of intrarow spacing on plant height was statistically insignificant in both years, while the effect of silage corn varieties on plant height was significant (P < 0.01). Turgut et al (2005), Iptas and Acar (2006), Azam et al (2007), and Yılmaz et al (2007) found that effects of plant density on plant height were statistically insignificant. According to the intrarow spacing, mean plant heights were found to be between 159.3 cm and 219.0 cm.…”
Section: Seed Emergencementioning
confidence: 99%